Relationship of Temperament and Character in Remitted Depressed Patients with Suicidal Ideation and Suicide Attempts—Results from the CRESCEND Study - Woo, Young Sup (Public Library of Science, 2014)
The aim of this study was to evaluate the Temperament and Character Inventory (TCI) scores of a sample of Korean patients with remitted depression who had attempted suicide and reported suicidal ideation and to compare their scores with those of remitted depressed patients without suicidal ideation. Adult depression patients who had completed 12 weeks of follow-up (N = 138) were divided into three groups: patients with a history of suicide attempts (N = 23); patients with current suicidal ideation (N = 59); and patients without current suicidal ideation (N = 56). After controlling for covariates, no significant differences were found among the three groups on any measure of temperament or character except self-directedness and self-transcendence. The self-transcendence scores of the lifetime suicide-attempt group were significantly higher compared with those of the suicidal-ideation group; post hoc analysis revealed that self-directedness was significantly lower in the suicide-attempt group compared with the non-suicidal group. The results from the present study suggest that remitted depression patients with a history of suicide attempts do not differ from non-attempters in temperament, but do differ in certain character traits.